1992
DOI: 10.1159/000263699
|View full text |Cite
|
Sign up to set email alerts
|

Detection of 47, XYY Trophoblast Fetal Cells in Maternal Blood by Fluorescence in situ Hybridization after Using Immunomagnetic Lymphocyte Depletion and Flow Cytometry Sorting

Abstract: Fluorescence in situ hybridization (FISH) allows to diagnose aneuploidy in uncultured interphase nuclei. This rapid method of chromosomal analysis associated with cell-sorting techniques was realized on 47, XYY fetal cells isolated from maternal blood. Trophoblast cells were sorted by combining immunomagnetic removal of maternal lymphocytes and flow cytometry sorting using antitrophoblast monoclonal antibodies. Cells were sorted directly on slides and analyzed by FISH with a Y-centromeric probe. Among 1,387 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 15 publications
0
32
0
1
Order By: Relevance
“…This could also explain why we were unsuccessful when using this antibody to identify trophoblast cells. Many fetal cell isolation approaches have been investigated, including positive selection of trophoblast cells [3,16,17] or selective depletion of maternal cells [18] , but the total numbers of isolated fetal cells remain too low for accurate prenatal diagnosis to take place. Although it is assumed that most fetal cells are probably rapidly removed from the maternal blood by the maternal immune system, a very small number of fetal cells will survive, probably by engrafting within specific maternal organs, and can be detected years post-partum [19] .…”
Section: Discussionmentioning
confidence: 99%
“…This could also explain why we were unsuccessful when using this antibody to identify trophoblast cells. Many fetal cell isolation approaches have been investigated, including positive selection of trophoblast cells [3,16,17] or selective depletion of maternal cells [18] , but the total numbers of isolated fetal cells remain too low for accurate prenatal diagnosis to take place. Although it is assumed that most fetal cells are probably rapidly removed from the maternal blood by the maternal immune system, a very small number of fetal cells will survive, probably by engrafting within specific maternal organs, and can be detected years post-partum [19] .…”
Section: Discussionmentioning
confidence: 99%
“…Cacheux et al were the first to report a chromosomal aberration (XYY) identified from trophoblasts retrieved from the maternal circulation using immunomagnetic depletion of leukocytes, and flow cytometry with the antitrophoblasts antibodies GB17 and GB25. However, only 4.25% of the nuclei analyzed by FISH showed a Y-signal [15]. Human leukocyte antigen G has also been successfully used to enrich circulating trophoblasts from maternal circulation and use those cells for aneuploidy detection [16][17][18].…”
Section: Trophoblastsmentioning
confidence: 99%
“…Chromosomal FISH allows the detection of aneuploidy and chromosomal rearrangements in interphase nuclei. It has been used to detect most of the major fetal aneuploidies within fetal cells isolated from maternal blood (28,(37)(38)(39). Fetal traits which have been identified so far among the separated fetal cells include blood group antigen, the common trisomies,…”
Section: Isolation Of Intact Fetal Nucleated Red Blood Cells In Matermentioning
confidence: 99%